Penggunaan Model Project Based Learning Untuk Menumbuhkan Karakter Gotong Royong Pada Mata Pelajaran Pendidikan Pancasila Kelas I di MI Sunan Ampel Gadingwatu Menganti Gresik - Kharisma Putri Dwi Anggraeni; Nur Hidayati; Noor Tatik Handayani (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
Character education is a critical focus in early childhood and primary education, including the development of collaboration and mutual cooperation as part of the Pancasila Student Profile. However, Civic Education in Grade I at MI Sunan Ampel Gadingwatu Menganti Gresik is still dominated by one-way, teacher-centered methods with limited student collaboration. This study aims to explore the implementation of the Project Based Learning (PjBL) model in fostering the value of cooperation among first-grade students through contextual and participatory learning. A descriptive qualitative approach was employed, with data collected through observation, interviews with the principal, teachers, and students, as well as documentation of project activities. The results reveal that PjBL enables students to share roles, communicate actively, and assist one another during group projects. The value of cooperation grows through habituation, shared responsibility, and positive peer interactions. Students showed behavioral shifts from individualistic tendencies to cooperative habits, supported by the teacher's role as a facilitator of character education. This study concludes that PjBL is not only effective in enhancing learning outcomes but also in building essential social values for primary education